Identifikasi Faktor Risiko Diabetes Melitus Tipe 2 pada Masyarakat Kampung Pelita Medika II, Desa Buluh Cina Kabupaten Kampar Provinsi Riau. - Suyanto Suyanto; Miftah Azrin (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2021)
The prevalence of Diabetes Mellitus (DM) type 2 in rural areas shows the higher case number in almost all regions in Indonesia. Increased fasting blood sugar levels, old age, high calorie diet and lack of physical activity are known risk factors for the incidence of type 2 diabetes. This study aims to identify risk factors for diabetes in the community by using an instrument in the form of checking fasting blood sugar levels with a glucometer, physical examination of anthropometry and filling out a questionnaire. The cross-sectional design was carried out on 235 respondents who lived in Kampung Pelita Medika II, Buluh Cina village, Kampar. It was found that 27.6% of respondents had fasting blood sugar levels of more than 125 mg / dL. Factors associated with the incidence of increased fasting blood sugar levels were female, had a body mass index of more than 25 kg / m2, and central obesity. Efforts to improve these risk factors need to be done and are expected to prevent future DM incidents from occurring.